Black fungus-gnats in deciduous forest habitat in northern Europe, with the description of Bradysia arcula sp. n. (Diptera: Sciaridae). - Vilkamaa, Pekka; Salmela, Jukka; Hippa, Heikki (2007)
The sciarid fauna of a deciduous forest in Kivijärvi Nature Reserve, southern Finland, was studied. In all, 58 species were found in a material of 247 specimens, collected with Malaise traps. The material included the following species new to the Finnish and North European fauna: Corynoptera postforcipata Rudzinski, Leptosciarella juniperi (Mohrig & Blasco-Zumeta), Leptosciarella subcoarctata Mohrig&Menzel, Leptosciarella yerburyi (Freeman), Phytosciara macrotricha (Lengersdorf) and Sciara nursei Freeman. Bradysia arcula sp. n., found also in two other localities in Finland, is described, and a key to the Finnish species of the Bradysia praecox group is provided
jufo
jufo:1
Hb0806
Keywords: taksonomia; lajinmääritys; Bradysia arcula; Diptera; kaksisiipiset; Sciaridae; harsosääsket; lehtimetsät; lajit; luettelot; Suomi; Finland; uudet lajit